Investigating domain structures and superdomains in ferroelectric PbTiO3 based heterostructures on DyScO3 - L. Tovaglieri; M. Hadjimichael; P. Torruella; C.-Y. Hsu; L. Korosec; D. T. L. Alexander; P. Paruch; J.-M. Triscone; C. Lichtensteiger (APL Materials, 2025)
This work focuses on the complex ferroelastic/ferroelectric domain structure in the prototypical ferroelectric PbTiO3 epitaxially strained on (110)o-oriented DyScO3 substrates, with a 22 nm-thick bottom SrRuO3 electrode. High quality epitaxial growth has been achieved from 7.2 nm (18 unit cells) up to 288 nm (720 unit cells) PbTiO3 film thickness. The evolution of the domain configuration and its scaling with the PbTiO3 film thickness are studied using a combination of atomic force microscopy, x-ray diffraction, piezoresponse force microscopy, and high resolution scanning transmission electron microscopy. A large asymmetry in the domain configuration is found due to the anisotropic strain imposed by the orthorhombic substrate. For thicker films, a larger scale arrangement of domains into superdomains is observed, with size that scales with the PbTiO3 film thickness, allowing a fine-tuning of their density. These superdomain structures affect the functional properties of the ferroelectric material and may play a role in switching devices such as memories. The presence of superdomains implies the existence of superdomain walls, which potentially exhibit properties intrinsically different from those of conventional ferroelastic or ferroelectric domain walls, opening the possibility of a new kind of superdomain wall-based nanoelectronics.